2008
DOI: 10.1007/s10529-008-9860-9
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro

Abstract: Human mesenchymal stem cells-like cells (hMSCs-like cells) were used as a tumor treatment platform for the systemic delivery of immunotoxin genes. VEGF165-PE38 recombinant immunotoxin served as the model system. hMSCs-like cells were isolated, expanded, and electroporated with the pIRES2-VEGF165PE38-EGFP plasmid. RT-PCR and ELISA were used to confirm the expression of VEGF165-PE38 in the transfected hMSCs-like cells. These cells released 1390 +/- 137 pg VEGF165-PE38/10(4)cells over 48 h into the culture medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…hMSCs were isolated and cultured as described previously 22. All cell lines were maintained in Dulbecco’s Modified Eagle’s Medium supplemented with 10% fetal bovine serum (Gibco, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…hMSCs were isolated and cultured as described previously 22. All cell lines were maintained in Dulbecco’s Modified Eagle’s Medium supplemented with 10% fetal bovine serum (Gibco, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…VEGF signals mainly through VEGF receptor 2 (VEGFR‐2), and VEGFR2 expression is restricted primarily to the vasculature endothelial cells engaged in tumor angiogenesis and is the key mediator of VEGF‐induced angiogenesis 7. Our previous studies have shown the direct effect of VEGF165‐PE38 recombinant immunotoxin on proliferation and apoptosis in human umbilical vein endothelial cells in vitro 8. Gene therapy as a delivery tool has been used repeatedly and has been proven to be effective in animal cancer treatment models 9–11.…”
mentioning
confidence: 99%
“…A high-titer stock of Ad-ephrinA1-PE38/ GM-CSF was obtained after three successive rounds of amplification and purification and then stored at −80°C. The level of ephrinA1-PE38/GM-CSF expressed was measured with a standard enzyme-linked immunosorbent assay (ELISA) as described elsewhere [17]. The absorbance was quantified at 450 nm using an ELISA reader (Molecular Devices, Sunnyvale, CA, USA) and the data were analyzed.…”
Section: Construction Of Plasmidmentioning
confidence: 99%